2015
DOI: 10.5213/inj.2015.19.2.120
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Lower Urinary Tract Symptoms on Quality of Life, Work Productivity, Depressive Symptoms, and Sexuality in Korean Men Aged 40 Years and Older: A Population-Based Survey

Abstract: Purpose:To examine the impact of lower urinary tract symptoms (LUTS) on health-related quality of life (HRQoL) in Korean men aged ≥40 years.Methods:A population-based, cross-sectional door-to-door survey was conducted among men aged ≥40 years. Individuals with LUTS were defined as men reporting at least one LUTS using 2002 International Continence Society definitions. Structuredquestionnaires were used to assess several dimensions of HRQoL, including generic health status (EuroQoL-five-dimensions questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 29 publications
3
45
0
1
Order By: Relevance
“…However, our results need to be interpreted with caution as we did not find evidence that absenteeism was associated with reduced work productivity although a significant difference in absenteeism was found between LUTS and control groups in one study . This is in line with previous studies, which reported that health conditions including LUTS impact more strongly on presenteeism than on absenteeism in males and mixed‐sex populations . Although risk factors associated with reduced work productivity have been identified in other patient populations, there is limited evidence on the risk factors in female workers with LUTS.…”
Section: Discussionsupporting
confidence: 82%
“…However, our results need to be interpreted with caution as we did not find evidence that absenteeism was associated with reduced work productivity although a significant difference in absenteeism was found between LUTS and control groups in one study . This is in line with previous studies, which reported that health conditions including LUTS impact more strongly on presenteeism than on absenteeism in males and mixed‐sex populations . Although risk factors associated with reduced work productivity have been identified in other patient populations, there is limited evidence on the risk factors in female workers with LUTS.…”
Section: Discussionsupporting
confidence: 82%
“…Men with ED are 1.33-6.24-times more likely to have BPH than men without ED [18,23,[31][32][33]35,57,[61][62][63] (Appendix S2 [14,18,23,[31][32][33]35,56,61,62,64,65]). Prevalence of ED and BPH ranged from 5.2% to 40% [64,65] and prevalence was positively associated with increasing age [64].…”
Section: Ed and Bphmentioning
confidence: 99%
“…It is defined as urinary urgency with or without urgency urinary incontinence and is usually associated with increased daytime frequency and nocturia (3). OAB has considerable impact on health-related quality of life (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%